DENOMINATIONAL AND LINGUISTIC GUARANTEES IN THE CANADIAN CONSTITUTION: IMPLICATIONS FOR QUEBEC EDUCATION - Burgess, Donald A. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1991)
This article is primarily concerned with an analysis of the constitutional protection provided under s. 93 of the Constitution Act of 1867 and of s. 23 of the relatively new Charter of Rights and Freedoms. The context is provided by three recent events: the Supreme Court decision on Mahé v. Alberta, the Quebec reference case on Bill 107, and the school board elections in Montreal. The author concludes that s. 23 of the Charter may add significantly to the protection afforded to minorities in s. 93. RÉSUMÉ Ce texte mise principalement sur l'analyse de la protection constitutionnelle accordée sous l'article s. 93 de la Loi sur la Constitution de 1867, et l'article s. 23 de la relativement récente Charte des droits et libertés. Le contexte est fondé sur trois événements récents: la décision de la Cour suprême sur Mahé c. l'Alberta, le cas de référence du Québec sur le projet de loi 107, et les élections de la commission scolaire de Montréal. L'auteur conclut que s. 23 de la Charte pourrait augmenter de façon très significative le degré de protection accordé aux minorités sous l'article s. 93.